It's Demographic Associated with Social Stigma of the Person with Covid-19 - Triyana Harlia Putri; Djoko Priyono (Universitas Aisyah Pringsewu, 2021)
Social stigma is a disaster and a burden for sufferers, survivors, families, health workers, or those closely related to the Covid-19 outbreak. Various levels of stigma affect almost all age groups, one being students. However, research on students' stigmatization and associated factors among people with Covid-19 in Indonesia are still limited. The purpose of this study was to identify the correlation between socio-demographic characteristics and stigma among students. This study used a cross-sectional-online design, with purposive and snowball sampling techniques with a sample size of 663 students. The questionnaire used was the Social Stigma toward Patients due to the Covid-19 Scale (SSPCS) questionnaire. Bivariate data analysis using Pearson and Spearman rank to see the socio-demographic correlation with stigma. Statistically, The experience of stigma discrimination, stigma not accepting, stigma fear, age, religion, and major are positively correlated ( p less than 0.01). This study found that not all socio-demographic factors relate to stigma. We only found age, religion, and major to correlate positively. Abstrak: Stigma sosial merupakan bencana dan beban bagi penderita, penyintas, keluarga, petugas kesehatan atau mereka yang terkait erat dengan wabah Covid-19. Berbagai tingkat stigma mempengaruhi hampir semua kelompok umur, salah satunya mahasiswa. Namun penelitian tentang stigmatisasi yang dirasakan mahasiswa dan faktor-faktor terkait pada penderita Covid-19 di Indonesia masih terbatas. Penelitian ini bertujuan mengidentifikasi hubungan antara faktor sosiodemografi dengan stigma pada mahasiswa. Studi ini juga menggunakan desain cross-sectional-online, dengan teknik purposive dan snowball sampling dengan jumlah sampel 663 siswa. Kuesioner yang digunakan adalah Kuesioner Social Stigma toward Patients due to Covid-19 Scale (SSPCS). Analisis data bivariat menggunakan Pearson dan Spearman rank untuk melihat korelasi sosiodemografi dengan stigma. Secara statistik, pengalaman diskriminasi, tidak terima, ketakutan, umur, agama, dan jurusan berkorelasi positif (p kurang dari 0.01). Studi ini hanya menemukan korelasi psitif antara karakteristik usia, agama dan jurusan mahasiswa dengan stigma.